PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN EKOWISATA ALAM BEREMBANG BERTUAH DI KAMPUNG SUAK MERAMBAI KECAMATAN BUNGARAYA KABUPATEN SIAK - Ayu Alsusanti; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The purpose of this study was to find out how the level of community participation in the development of Ecotourism in Developing Sorcerer Nature and what factors hampered community participation in Kampung Suak Merambai, Bungaraya Subdistrict, Siak Regency consisted of four dimensions, namely planning, implementation, utilization of results and evaluation. The research method used in this research is descriptive quantitative method. The sample in this study were 63 people using purposive probability sampling techniques. Data sources from this study are primary data and secondary data obtained from observations, questionnaires, interviews, and documentation. By using an instrument measurement scale that is Likert scale. The data analysis technique used is descriptive statistics. Based on research shows that the level of community participation in the development of Ecotourism Growing Sorcerer in the Village of Suak Merambai, Bungaraya District, Siak Regency is included in the medium category in the aspects of planning, implementation, utilization of results, and evaluation. Keyword: Community participation, tourism development, ecotourism